Legal Protection of Intellectual Property Rights: What is Urgency for The Business World? - Zulfikri Zulfikri; Zulkarnaini Zulkarnaini (Jurnal IUS Kajian Hukum dan Keadilan, 2022)
Thought intellectual works produced by humans that require the sacrifice of energy, time, and cost in its creation. The existence of this sacrifice makes the work produced has economic value because of the benefits it enjoys. Based on this concept, it encourages the need for an appreciation for the work in the form of legal protection for Protection of Intellectual Property Rights (IPR). This paper aims to analyze the Legal Protection of IPR and Its Urgency for the Business World. This research uses a legal policy approach, namely an approach that is carried out by observing the laws and regulations related to the policy issues under study. The results of the research show that Intellectual Property Rights products are works born of creativity, initiative, and creative power, as well as high and creative intellectual abilities/the work of the brain, meaning and reasoning from the inventors, creators and designers. The results of intellectual creativity with such a deep process as mentioned above have a very high economic value. The results of these works are essentially the personal wealth of those who invented, created or designed.